Orofacial Coordination: How do we walk and chew gum at the same time? - Morquette, Philippe; Kolta, Arlette (eLife, 2014)
A genetic approach has been used to map the neural circuits that control and coordinate the tongue and jaw muscles.
Keywords: premotor circuit; monosynaptic rabies virus; jaw motoneuron; tongue motoneuron; orofacial coordination